Intrinsic distortion of a fully differential BD-modulated Class-D amplifier with analog feedback - Cox, Stephen M.; Yu, J.; Goh, W.L.; Tan, M.T. (IEEE, 2013)
This paper presents a mathematical analysis of a fully differential BD-modulated Class-D amplifier with analog feedback, i.e., one having a bridge-tied-load output configuration with negative feedback and ternary PWM signal. Notwithstanding the highly nonlinear nature of the amplifier's operation, an extremely accurate closed-form expression for the audible output signal is derived and verified based on computer simulations. This expression demonstrates that there exist larger high-order intrinsic distortions (e.g., 5th-order harmonic distortion and intermodulation distortion) for BD-modulation, compared to that for AD-modulation (binary PWM signal). Furthermore, the 3rd-order harmonic distortion has a roughly parabolic response as a function of the magnitude of the input signal and reaches its peak when the modulation index of the input signal is around 0.7. Overall, the BD-modulated Class-D amplifier has a larger intrinsic distortion for small input signal but a smaller intrinsic distortion for large input signal, compared to AD-modulated designs.